The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1037/0735-7028.39.1.93
|View full text |Cite
|
Sign up to set email alerts
|

Lessons from Katrina: Disaster mental health service in the Gulf Coast region.

Abstract: In this article, 4 mental health professionals provide firsthand accounts of experiences as volunteers in the Gulf Coast region following Hurricanes Katrina and Rita in the fall of 2006. These accounts are provided with the goal of informing psychologists and other mental health providers about the role of volunteers from a frontline perspective. The authors offer these observations as a compliment to formal training in disaster preparedness that psychologists might receive for volunteer service in the wake of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 12 publications
0
24
0
Order By: Relevance
“…Disaster intervention research has identified groups likely to be at greater psychosocial risk, including women, children, the elderly, the rural and urban poor, racial and ethnic minorities, those with a previous history of emotional disability, inhabitants of developing rather than developed countries, and in general, those with a marginalized predisaster existence (Haskett, Scott, Nears, & Grimmett, 2008;Norris, Friedman, Watson, Byrne, et al, 2002). In terms of climate change, individuals with mental illness are particularly vulnerable to heat-related injury and mortality due to risk factors such as the use of psychotropic medication, preexisting respiratory and cardiovascular disease, substance misuse, and poor quality housing (Page & Howard, 2010).…”
Section: Vulnerability and Resiliencementioning
confidence: 99%
“…Disaster intervention research has identified groups likely to be at greater psychosocial risk, including women, children, the elderly, the rural and urban poor, racial and ethnic minorities, those with a previous history of emotional disability, inhabitants of developing rather than developed countries, and in general, those with a marginalized predisaster existence (Haskett, Scott, Nears, & Grimmett, 2008;Norris, Friedman, Watson, Byrne, et al, 2002). In terms of climate change, individuals with mental illness are particularly vulnerable to heat-related injury and mortality due to risk factors such as the use of psychotropic medication, preexisting respiratory and cardiovascular disease, substance misuse, and poor quality housing (Page & Howard, 2010).…”
Section: Vulnerability and Resiliencementioning
confidence: 99%
“…Most of the literature related to the impact and subsequent recovery from natural disasters examines the impact of the disaster on children (Madrid & Grant, 2008;Tuicomepee & Romano, 2008), whereas other researchers focus on the mental health needs of individuals immediately following natural disasters (Cohan & Cole, 2002;Haskett, Scott, Nears, & Grimmett, 2008;Jones, Immel, Moore, & Hadder, 2008;Jordan, 2002;Levy, 2008). Few, however, focus on providing life planning (Peavy, 1996) to adult survivors of natural disasters 3 months to 1 year following the event.…”
Section: Adult Disaster Survivorsmentioning
confidence: 99%
“…When humanitarian agencies initially respond to a catastrophic event, immediate services are provided by first responders. First responders are people who live in the area (ARC, 2011), who balance their own needs and responsibilities while providing food, shelter, and clothing to other survivors (Haskett et al, 2008) and offering comfort to close family members (Terr, 1992). The primary focus of humanitarian agencies is the provision of basic needs for individuals by first responders (ARC, 2011;Haskett et al, 2008;Jones et al, 2008;Madrid & Grant, 2008).…”
Section: Short-and Long-term Supportsmentioning
confidence: 99%
“…We referred to these as “key lessons” or “best lessons.” Norcross () used similar terminology to study the “lasting lessons” that psychotherapists reported from undertaking personal psychotherapy. Haskett, Scott, Nears, and Grimmett () described lessons learned from their experience as volunteer mental health workers in the aftermath of Hurricane Katrina. Humphreys () elucidated the “basic lessons of psychology” that infused mental health initiatives related to the Iraq war.…”
mentioning
confidence: 99%